2019
DOI: 10.2991/ijndc.k.190917.001
|View full text |Cite
|
Sign up to set email alerts
|

A Secure and Scalable Data Source for Emergency Medical Care using Blockchain Technology

Abstract: KeywordsPermissioned blockchain network emergency medical care scalable blockchain A B S T R A C TA relationship exists between the emergency patient death rate and factors such as the failure to access a patient's critical data and the time it takes to arrive at hospitals. The ability for Paramedics to access a patient's complete picture of emergency-relevant medical data is critical and can significantly reduce the annual mortality rate. Today, the problem exists with a continuous recording system of the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
8
0
Order By: Relevance
“…Currently, ethernet and hyper ledger fabric are the most popular frameworks. Hasavari et al [ 16 ] showed that hyper ledger fabric is the most effective frame structure combined with medical treatment at present. One solution to the problem regarding the combination of blockchain and medical treatment is to replace patient care reports with electronic health records (EHRs) so that they can interoperate with other EHRs.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, ethernet and hyper ledger fabric are the most popular frameworks. Hasavari et al [ 16 ] showed that hyper ledger fabric is the most effective frame structure combined with medical treatment at present. One solution to the problem regarding the combination of blockchain and medical treatment is to replace patient care reports with electronic health records (EHRs) so that they can interoperate with other EHRs.…”
Section: Resultsmentioning
confidence: 99%
“…Blockchain has been described as a concept that guarantees suitability, immutability, and nonrepudiation (Sivaram et al, 2020). Thus, it is a technology that focuses on streamlining the proper flow of information for use (Hasavari & Song, 2019) and is posted to it as an unchangeable truth (Schuetz & Venkatesh, 2020). In the influential work available in 2008, Bitcoin: a peer-to-peer electronic money arrangement, Satoshi Nakamoto defines blockchain technology's support (Smith & Dhillon, 2017).…”
Section: Adoption Of Blockchain Technologymentioning
confidence: 99%
“…It will maintain unmodifiable and incessantly growing information records. The dealings are a fundamental concept in Blockchain, unique information wherever transactions are often value-added but not deleted, and the operations area unit is recorded as transactions (Hasavari & Song, 2019). The stored data could be payment history, e.g., Bitcoin, a contract, or personal information (Dorri et al, 2019).…”
Section: Characteristics Of Blockchain Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Liu et al [10] presented a healthcare insurance anti-fraud system based on blockchain. A hybrid architecture to facilitate access control of medical data was developed in [11]. A blockchain is used to manage identity and access control and acts as a tamper-proof log of access events.…”
Section: Literatures Surveysmentioning
confidence: 99%